Titanium addition influences antibacterial activity of bioactive glass coatings on metallic implants. Issue 10 (October 2017) - Rodriguez, Omar; Stone, Wendy; Schemitsch, Emil H.; Zalzal, Paul; Waldman, Stephen; Papini, Marcello; Towler, Mark R.
Abstract: In an attempt to combat the possibility of bacterial infection and insufficient bone growth around metallic, surgical implants, bioactive glasses may be employed as coatings. In this work, silica-based and borate-based glass series were synthesized for this purpose and subsequently characterized in terms of antibacterial behavior, solubility and cytotoxicity. Borate-based glasses were found to exhibit significantly superior antibacterial properties and increased solubility compared to their silica-based counterparts, with BRT0 and BRT3 (borate-based glasses with 0 and 15 mol% of titanium dioxide incorporated, respectively) outperforming the remainder of the glasses, both borate and silicate based, in these respects. Atomic Absorption Spectroscopy confirmed the release of zinc ions (Zn 2+ ), which has been linked to the antibacterial abilities of glasses SRT0, BRT0 and BRT3, with inhibition effectively achieved at concentrations lower than 0.7 ppm. In vitro cytotoxicity studies using MC3T3-E1 osteoblasts confirmed that cell proliferation was affected by all glasses in this study, with decreased proliferation attributed to a faster release of sodium ions over calcium ions in both glass series, factor known to slow cell proliferation in vitro .